The association of uncoupling protein 2 (UCP2) exon 8 insertion/deletion polymorphism and ECG derived QRS duration: A cross-sectional study in an Australian rural population. (1st February 2017) - Lee, Yvonne Yin Leng; Zhou, Yuling; Jelinek, Herbert F; Hambly, Brett D; McLachlan, Craig S
Abstract: Background: Associations between inherited mitochondrial disease and cardiac conduction have been previously described. However, there are no available studies exploring the mitochondrial uncoupling protein 2 gene (UCP2) insertion/deletion (I/D) polymorphisms interaction on cardiac electrical conduction. Our aim was to determine if ECG-derived QRS duration is associated with UCP2 DD genotype in a cross-sectional Australian aging rural population. Methods: A retrospective study design utilizing a rural health diabetic screening clinic data-base containing observational data from September 2011 to September 2014. Inclusion criteria included were having ECG parameters such as QRS duration measures and a DNA sample within the same subject. Genomic DNA was extracted and subjects were genotyped for the 45-bp I/D polymorphism in the 3′-untranslated region of UCP2. Results: 281 individuals were available for analysis. On the basis of QRS duration > 140 ms we found an increased percentage of our population with DD homozygotes, compared to ID heterozygotes and II homozygotes (p = 0.047). For other ECG parameters; mean PQ duration, QTc across UCP2 genotypes was not significant (p = NS). QTc using a cut-off > 440 ms in contingency table analysis revealed no significant differences across UCP2 I/D genotypes. Mean QT dispersion (QTd) was paradoxically less in the UCP2 DD genotype compared to UCP2 II subgroup (p = 0.034). Discussion: We have demonstrated an association between increasing ECG-derived QRS duration > 140 ms and the UCP2 DD polymorphism. The lack of association with ECG derived QTd and UCP2 DD may suggest that gene-related QRS duration prolongation is independent of cardiac hypertrophy.